Le recrutement des professeurs des écoles : un effet IUFM ? - Christophe Michaut (Recherches en Éducation)
Many studies focus on teachers’ work (Maroy, 2005), their professional practice, their roles in schools, their identity (Rayou & van Zanten, 2004) or their professional socialization (Guibert, Lazuech & Rimbert, 2008), but very little on their recruitment, while 45% of primary teachers are expected to retire between 2003 ad 2013 (Evain, 2005). The article focuses on the recruitment of candidates at the school teacher’s examination. Candidates can prepare in an IUFM or present themselves as independent candidate. The aim here is to evaluate the IUFM effect, that is the added value IUFM brings in the chances of success in examination over applicants who have not benefited from this preparation, from a progress report of candidates registered for entrance examinations of a IUFM (N=1266) to their admission into the teaching profession. The results show all things being equal that students training at IUFM are four times more likely to be successful in the examination as private candidate. This highly significant effect of IUFM is partly due to pre-recruitment of candidates best equipped to pass the tests of the examination.